Antibody Competition Reveals Surface Location of HPV L2 Minor Capsid Protein Residues 17–36 - Stephanie M. Bywaters; Sarah A. Brendle; Kerstin P. Tossi; Jennifer Biryukov; Craig Meyers; Neil D. Christensen (Viruses, 2017)
The currently available nonavalent human papillomavirus (HPV) vaccine exploits the highly antigenic L1 major capsid protein to promote high-titer neutralizing antibodies, but is limited to the HPV types included in the vaccine since the responses are highly type-specific. The limited cross-protection offered by the L1 virus-like particle (VLP) vaccine warrants further investigation into cross-protective L2 epitopes. The L2 proteins are yet to be fully characterized as to their precise placement in the virion. Adding to the difficulties in localizing L2, studies have suggested that L2 epitopes are not well exposed on the surface of the mature capsid prior to cellular engagement. Using a series of competition assays between previously mapped anti-L1 monoclonal antibodies (mAbs) (H16.V5, H16.U4 and H16.7E) and novel anti-L2 mAbs, we probed the capsid surface for the location of an L2 epitope (aa17–36). The previously characterized L1 epitopes together with our competition data is consistent with a proposed L2 epitope within the canyons of pentavalent capsomers.